Early upregulation of immune suppressors dominates the macrophage response to Toxoplasma gondii - Dominykas Murza; Filip Lastovka; George Wood; Matthew P. Brember; Oliver Chan; James W. Ajioka; Betty Y. W. Chung (PLoS ONE, 2025)
The apicomplexan parasite Toxoplasma gondii is a master manipulator, subverting its host through secreted proteins, hormone disruption, and even behavioural changes. Macrophages, the immune system’s first responders, play a pivotal role in determining infection outcomes, yet the initial triggers shaping these complex responses remain elusive. This study unveils the earliest transcriptional shifts in a mouse macrophage-like cell line RAW264.7- T. gondii infection model. Using time-resolved transcriptomic profiling, we captured host and parasite gene expression dynamics within the critical 15–120 minute window — when the host mounts its first line of defence and the parasite secures its foothold. By leveraging inactivated parasites, we disentangled responses to active invasion from general immune activation. By 60 minutes, macrophages exhibited a trend of increased suppressor of cytokine signalling expression — uniquely tied to live infection — while stress and pro-growth genes became dysregulated. Meanwhile, T. gondii responded with a slow but strategic transcriptional shift: an early increase in transcription and growth capacity, followed by a delayed activation of secreted proteins. These findings reveal a tug-of-war at the transcriptional level, where macrophages show rapid upregulation, while T. gondii employs a measured, delayed strategy to carve out its replicative niche.